Efektivitas Microlearning Untuk Meningkatkan Konsentrasi Belajar Siswa Sekolah Dasar - Dimas Pratama; Intan Maharani; Rendi Kurniawan (FONDASI: Jurnal Pendidikan Dasar, 2026)
Abstract This study aims to examine the effectiveness of microlearning in improving elementary school students’ learning concentration and its impact on engagement and content understanding. The study was motivated by the persistent problem of students’ limited attention span during classroom instruction, which affects participation and learning outcomes. A quasi experimental approach with a pretest and posttest design was employed involving elementary school students as research participants. The intervention was conducted through microlearning implementation based on content segmentation, short learning activities, and interactive visual media over six weeks of instruction. The findings revealed a significant improvement in students’ concentration following the implementation of microlearning. Students were able to maintain attention for longer periods, showed reduced distraction, and responded more quickly to instructional directions. Learning engagement also increased as reflected in active participation during discussions, greater willingness to ask questions, and consistent task completion. Improved concentration and engagement contributed to better content understanding, as indicated by higher formative assessment scores and more accurate concept application. The results confirm that microlearning creates focused and active learning experiences aligned with the developmental characteristics of elementary school students who typically possess limited attention spans. Microlearning also supports teachers in managing instructional pacing and providing immediate feedback. When designed appropriately, microlearning has strong potential as an alternative instructional strategy to enhance both learning processes and outcomes in elementary education.